Effects of four soybean meal products on lactational performance of dairy cows - M.S. Awawdeh; Evan C. Titgemeyer; James S. Drouillard; John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 2006)
Thirty-two multiparous Holstein cows (152 days in milk, producing 90 lb/day of milk at the beginning of the study) were used in a 4 x 4 Latin square design with 28-day periods to investigate cow responsiveness to supple-mental ruminally undegraded protein from 4 soybean meal products. The 4 products were: solvent soybean meal (SSBM), expeller soy-bean meal (ESBM), lignosulfonate-treated soybean meal (LSBM), and SSBM treated with 0.05% baker's yeast and toasted at 212ºF (YSBM). Diets were formulated by substitut-ing all SSBM and part of ground corn with YSBM, ESBM, or LSBM to yield isonitroge-nous diets. Diets were formulated to provide adequate ruminally degraded protein, but defi-cient ruminally undegraded protein and me-tabolizable protein supplies. No differences among dietary treatments were observed for dry matter intake, body weight gain, milk and component yields, or efficiency of milk pro-duction. Lack of response to changes in soy-bean meal source was likely because of ade-quate ruminally undegraded protein and me-tabolizable protein supply by all diets.; Dairy Day, 2006, Kansas State University, Manhattan, KS, 2006;
Keywords: Dairy Day; 2006; Kansas Agricultural Experiment Station contribution; no. 07-118-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 965; Dairy; Protein; Soybean meal